2019
DOI: 10.1108/jbim-01-2018-0057
|View full text |Cite
|
Sign up to set email alerts
|

Transaction-specific investments in a supplier-distributor-supplier triad in China: opportunism and cooperation

Abstract: Purpose Rather than focussing on dyadic distributor–supplier relationships, this study aims to examine whether the difference in transaction-specific investments (TSIs) between rival suppliers in a supplier–distributor–supplier triad influences whether distributors expropriate or maintain their supplier’s TSIs. Design/methodology/approach Drawing on triadic data from 276 questionnaires that address both the supplier–distributor relationship and the rival supplier–distributor relationship, a moderated regress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 79 publications
0
7
0
Order By: Relevance
“…Considering that specific investments expose firms to opportunism (Liu et al, 2019) it is in the best interest of those making such investments to find ways of protecting themselves. The fact that a firm may be dealing with a business partner that they are non-economically satisfied, may not provide adequate protection against exposure of specific investments to opportunistic behavior.…”
Section: Formalization and Specific Investmentmentioning
confidence: 99%
“…Considering that specific investments expose firms to opportunism (Liu et al, 2019) it is in the best interest of those making such investments to find ways of protecting themselves. The fact that a firm may be dealing with a business partner that they are non-economically satisfied, may not provide adequate protection against exposure of specific investments to opportunistic behavior.…”
Section: Formalization and Specific Investmentmentioning
confidence: 99%
“…The fact that specific investments expose the investing partner to a high opportunism risk (Liu et al, 2019;V azquez-Casielles et al, 2017) means that a business would want to make sure that adequate protective mechanisms are in place before making any moves in this direction. One important way in which businesses can protect themselves from opportunistic behaviour by business partners is through having rules that prescribe acceptable and unacceptable behaviours and clearly define the roles and responsibilities of each partyi.e.…”
Section: Formalisation Specific Investment and Dependencementioning
confidence: 99%
“…Durach et al ( 2020 ) formulated a tetradic relationship, going one step further from the triadic relationship, and empirically confirmed that co-opetition between 1 st tier suppliers has a positive effect on the capability to discover and respond to risks occurring from 2 nd tier suppliers. Liu et al ( 2019 ) demonstrated that in the triadic relationship of buyer–supplier 1–supplier 2 downstream of the supply chain, the transaction-specific investment (TSI) of supplier 1 triggers the buyer’s opportunistic behavior, and if the TSI level of supplier 2 is higher, the opportunistic behavior expands further.…”
Section: Literature Reviewmentioning
confidence: 99%